Systematic purchase behaviour in big transactional data: measurement innovations and applications - Mansilla, Roberto (2024)
With the rapid advancement in technology and the emergence of new sources of data, consumer buying behaviours have become increasingly dynamic. This has created a growing need for new measures and models to understand and predict complex buying patterns, aiming to enhance customer experience, satisfaction, and loyalty.